Downsize this! - Moore, Michael 1954 April 23- (New York, NY Harper Collins Publishers, Inc., 1997)
The author takes on the corporate and political powers that be, setting his sights on astronomical CEO salaries, downsizing for fun and profit, and other contemporary maladies.
Ch. 1. Let's all hop in a ryder truck -- ch. 2. Would Pat Buchanan take a check from satan? -- ch. 3. "don't vote -- it only encourages them" -- ch. 4. Democrat? Republican? Can you tell the difference? -- ch. 5. Not on the mayflower? Then leave! -- ch. 6. Big welfare mamas -- ch. 7. Let's dump on orange county -- ch. 8. How to conduct the Rodney king commemorative riot -- ch. 9. Pagan babies -- ch. 10. Germany still hasn't paid for its sins -- and i intend to collect -- ch. 11. So you want to kill the president! -- ch. 12. Show trials i'd like to see -- ch. 13. If Clinton had balls ... -- ch. 14. Steve Forbes was an alien -- ch. 15. Corporate crooks trading cards -- ch. 16. Why are union leaders so f♯!@ing stupid? -- ch. 17. Balance the budget? Balance my checkbook! -- ch. 18. Mike's penal systems, inc. -- ch. 19. Mandate? What mandate? -- ch. 20. My forbidden love for Hillary -- ch. 21. A sperm's right to life -- ch. 22. Let's pick a new enemy! -- ch. 23. Those keystone Cubans -- ch. 24. What America needs is a makeover -- ch. 25. O. J. Is innocent -- ch. 26. O. J. Is guilty -- ch. 27. The "liddy problem" -- ch. 28. I try to commit Bob Dornan -- ch. 29. Skip the candidates -- vote for the lobbyists! -- ch. 30. Harassing gays for extra credit -- ch. 31. Take that pen out of bob dole's hand -- ch. 32. Free us, nelson Mandela! -- ch. 33. Nafta's great! Let's move Washington to Tijuana! -- ch. 34. Why doesn't gm sell crack? -- ch. 35. I want my tax break or i'm leaving -- ch. 36. Ten ways to downsize the boss -- ch. 37. Mike's militia -- everyone fired ... Wall street reacts favorably.
Includes new introduction, epilogue, and some updated text.
Includes bibliographical references.
Originally published
Keywords: American wit and humor; United States -- Politics and government -- 1993-2001 -- Humor; United States -- Social conditions -- 1980- -- Humor